PROBLEMATIK BAHAN AJAR DALAM PEMBELAJARAN SASTRA YANG BERORIENTASI PADA RESPONS PEMBACA - Rumasi Simaremare (BAHAS, 2010)
Dissatisfaction will process and results of teaching literature in schools is a classic problem which until now has not fully resolved. As a system, problems occurred in the teaching of literature can be approached from the factors that shape the teaching of literature itself. Forming factors that are teachers, students, curriculum, methods, facilities and infrastructure, and materials. External elements such as the demands of even the people (both laymen and literary society) and policy makers of formal education (starting from the formulation of the Guidelines to guide the implementation of curriculum tennis) helped contribute to the emergence of problematic. Kata Kunci : bahan ajar sastra, pembaca